2016
DOI: 10.1039/c6ra17059e
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effect of Bletilla striata extracts on LPS-induced acute lung injury by regulation of inflammation and oxidation

Abstract: Identification of active ingredients, and their structures, from Bletilla striata and investigation of the antioxidative and anti-inflammatory responses in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Treatment with BG@BSA NPs reduced MDA and increased SOD in the lung. Similar results have been documented using BM 60 [25].…”
Section: Antioxidant Activitysupporting
confidence: 89%
See 2 more Smart Citations
“…Treatment with BG@BSA NPs reduced MDA and increased SOD in the lung. Similar results have been documented using BM 60 [25].…”
Section: Antioxidant Activitysupporting
confidence: 89%
“…However, the lung wet/dry ratios were greatly decreased in animal treated with BG@BSA NPs, thus con rming the protective effect of BG@BSA NPs. BM60 decreased the lung wet-to-dry ratio, which suggested the protective effect on LPS-induced ALI [25].…”
Section: Effect Of Bg@bsa Nps On Cell Viability and No Productionmentioning
confidence: 81%
See 1 more Smart Citation
“…We found that Wang et al [43] also reported an antiinflammatory, antioxidant system regulating an active part of Bletilla striata. Briefly, the 95% ethanol extract of Bletilla striata was fractionated by systematic solvent; then, the ethyl acetate fraction was eluted by gradient ethanol on MCI column chromatography, combined with total phenol content and DPPH free radical scavenging activity screening; an active fraction BM60 was obtained and characterized by HPLC-ESI-HRMS.…”
Section: Discussionsupporting
confidence: 53%
“…As the synthesis of MIPs is also relatively easy and cheap, they are a preferred substitute for natural receptors and have been widely used in the elds of chromatography, solid phase extraction, chemical sensors, etc. 24,25 However, with free radical polymerization methods, the rate of chain growth cannot be controlled, and side reactions during chain transfer and chain termination cause substantial variation in the size of the polymer, 26 making it difficult to prepare conventional MIPs. Living/ controlled free radical polymerization methods such as surfaceinitiated atom transfer radical polymerization (SI-ATRP) can produce more uniform polymers by controlling the rate of chain growth.…”
Section: Introductionmentioning
confidence: 99%